Giant torturous left circumflex artery draining to the right atrium - Eremiasova, Lenka; Kuchynka, Petr; Lambert, Lukas; Palecek, Tomas (Echocardiography, 2017)
Coronary artery anomalies represent a diverse group of congenital disorders characterized by abnormalities of coronary arteries anatomy. We describe an extremely rare case of giant torturous left circumflex artery draining to the right atrium manifesting by palpitations and atrial fibrillation.
Keywords: Severity of Illness Index; Tomography, X-Ray Computed; echokardiografie transezofageální; srdeční síně; mužské pohlaví; Humans; koronární cévy; stupeň závažnosti nemoci; Coronary Vessel Anomalies; anomálie koronárních cév; Echocardiography, Transesophageal; Coronary Angiography; lidé; počítačová rentgenová tomografie; koronární angiografie; Diagnosis, Differential; senioři; diferenciální diagnóza; Heart Atria; Aged; Coronary Vessels; Male